A new species of Clidicus with asymmetrical parameres (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
Clidicus Laporte, 1832 currently comprises 27 species distributed in India (Karnataka, Tamil Nadu), Sri Lanka, Indonesia (Java, Kalimantan, Sumatra), Malaysia (Sabah, Sarawak), Laos, Vietnam, the Philippines (Mindanao), China (Hainan) and Australia (Queensland). Some species have conspicuously large adults reaching 8.5 mm, and they represent the largest known Scydmaeninae. Species of Clidicus were relatively poorly known until recently, when Orousset (2014) revised a large portion of this genus and described several new species. Other major studies include Besuchet (1971), who described Sri Lankan species, Jałoszyński et al. (2003) who recorded four new species from Vietnam and Laos, Jałoszyński (2009) with the first description of a Philippine species, and Zhou & Li (2015), who discovered the first species in China. Another new species, representing the second Clidicus occurring in the Philippines, is described below.